Experimental study on anti-drift shield curtain device for soybean (Glycine max)-maize (Zeal mays) strip intercropping weed sprayers - Yuxuan Jiao; Qingqing Zhou; Tao Sun; Chen Cai; Longfei Cui; Zhu Sun; Yongkui Jin; Wei Kong; Suming Ding; Xinyu Xue (PLoS ONE, 2025)
Soybean-maize strip intercropping is an important method to increase soybean oil self-sufficiency and promote sustainable agricultural development, which has rapidly developed in China in recent years. However, the herbicides used in the post-emergence weeding stage of soybean and maize can inhibit each other's growth, and herbicide drift can easily lead to crop yield reduction or even death. To reduce the drift risk of soybean-maize strip intercropping sprayers during the post-emergence weed control stage, we explored the efficacy of shield curtain device in reducing drift through wind tunnel and field trials. The study found that when only two sides of shield curtains were used to cover the spray area in the wind tunnel test, the maximum drift rate was 2.18% under the influence of lateral airflow, while drift was more severe under the influence of inter-row airflow with a maximum drift rate of 14.99%. The drift rate far exceeded the threshold causing herbicide damage on soybeans and maize. In the field test, using shield curtains on the front, back, and both sides of the spray area could obtain a maximum spray drift rate of 0.98% and a minimum deposition rate of 57.87%. This approach could reduce the drift rate by more than 88.5% and increase the deposition rate by more than 47.2% compared to not using the shield curtain device. The study can offer valuable reference and data support for the research of anti-drift technology for soybean-maize strip intercropping sprayers and provide ideas for designing shield devices.